Photochemical reduction of carbonyl group of polyimide by 450 nm diode laser. (November 2019) - Roslan, M S; Kamarudin, H; Sharip, N; Zin, A F M; Muhamad, A; Agam, A; Nayan, N; Tariq, U
Abstract: In this article, we report directly patterned graphene nanoribbons by laser irradiation. The transformation of polymer into graphene nanostructure by breaking oxygen bonding and followed by graphitization of carbon atoms has been employed by using the photochemical technique. The scalable and fast growth of graphene nanoribbon was carried out by irradiating 450 nm diode laser directly onto polyimide polymer. Patterned graphene was characterized by Raman spectroscopy, Fourier transform infrared spectroscopy (FTIR) and Field emission scanning electron microscopy (FESEM). The ability of polyimide to absorb laser light in the near-ultraviolet region contribute to the tailoring of graphene nanoribbon which reduces oxygen bonding as well as paves way for the development of optoelectronics applications.